PWE-034 Patient-reported Experience Of Comfort And Dignity In Flexible Sigmoidoscopy: Data From The Nhs Bowel Scope Screening Pilot. (9th June 2014) - Von Wagner, C; Bowyer, H; Rees, CJ; Atkin, W; Wardle, J
Abstract : Introduction: The NHS Bowel Cancer Screening Programme started flexible sigmoidoscopy (FS) screening (also known as Bowel Scope Screening, BSS) at six centres across England (Gateshead, Guildford, London, Medway, Norwich, Wolverhampton) in March 2013. The aim of this analysis was to investigate the extent to which high levels of patient satisfaction recorded in previous UK trials can be replicated in the early stages of a routine screening programme. Methods: We used used data from an ongoing study monitoring patient-reported experience in the pilot phase of the BSS Programme. We report data from the 'post-AM questionnaire' which is given to patients at the end of their FS appointment and supposed to be completed on the following day. Results: As of January 2014, we had received 2, 324 questionnaires. Satisfaction with the test was high with 98.8% of patients being either satisfied (21.1%) or very satisfied (77.7%). Nonetheless, 43% of patients reported moderate (34%) or severe pain (9%) which was high compared with the St Marks' demonstration programme 1 and the UK Flexible Sigmoidoscopy Trial 2 (Figure 1 ). Women were three times as likely to report severe pain during the test than men (14.3 vs 4.6%), and twice as likely to find the test as more painful than they had expected (39.9 vs 20.1% respectively). Only about 1 in 10 patients reported being moderately (9.8%) or severely (1.4%) embarrassed during the test, with women being slightly more likely than men to fall into these categories (13.4 vs. 8.9%). Women also had a much stronger preference for the test to be carried out by a female practitioner than men (41.2% vs 7.1% respectively). Conclusion: The vast majority of patients were satisfied with their experience of FS screening. However, levels of pain appear high when compared with previous trials. Emphasis should be placed on ensuring that patients have as comfortable a procedure as possible. Additional consideration should be given to women being able to choose the sex of the practitioner performing the test. References: 1 Robb K, Lo S, Power E, et al . Patient-reported outcomes following flexible sigmoidoscopy screening for colorectal cancer in a demonstration screening programme in the UK. J Med Screen 2012;19:171–176 2 Taylor T, Williamson S, Wardle J, et al . Acceptability of flexible sigmoidoscopy screening in older adults in the United Kingdom. J Med Screen 2000;7:38–45 Disclosure of Interest: None Declared.